P245 A dedicated pneumonia follow up clinic–is it worthwhile?. (14th November 2013) - Komrower, D; Iyer, S; Kazmi, S; Shanker, V; Stockton, P; Twite, S; Malhotra, P
Abstract : Background: It is routine clinical practice, based on British Thoracic Society recommendations, to arrange a clinical review and chest x-ray approximately 6 weeks following an episode of pneumonia in most patients. However there is a paucity of published evidence to support or refute this practice. Objective: To determine the clinical and radiological outcomes of patients admitted with an episode of pneumonia. Methods: This was a retrospective analysis of the post-pneumonia clinic database at a large district general hospital over a one year period from May 2011 to April 2012. Data on demographic characteristics, radiological and clinical follow up, and final diagnosis were collected. Follow up data including a new diagnosis of cancer as well as new benign lung disease was available for most (97%) patients for 12 months after the index episode of pneumonia. Resolution was defined as complete resolution on chest X-ray at 6–8 weeks or >90% resolution on chest X-ray, absence of ongoing physical symptoms and signs, and decision to discharge from clinic after discussion at a multi-disciplinary radiology meeting. Results: 179 patients were included in the analysis (32 who did not attend for follow up were excluded). One hundred and thirty nine (78%) showed resolution and were discharged. Of the 40 (22%) patients that did not show resolution, 16 (9%) had a new diagnosis made; including 3 (1.7%) lung cancer. One of the identified lung cancers was stage I disease, while the other two were stage IV. New benign diagnoses made on follow up were recurrent aspiration (3), interstitial lung disease (2), pleural effusion (2), allergic bronchopulmonary aspergillosis (1), cryptogenic organising pneumonia (1), functional antibody deficiency (1), lung nodule (1), pleural plaques (1), and pulmonary embolism (1). Males, ever smokers, older patients, and those with a history of pre-existing lung disease (including COPD) had higher rates of non-resolution but the differences were not statistically significant. Conclusion: Following up patients in a dedicated post pneumonia clinic with a repeat chest radiograph and clinical review had a low but significant pick up rate of new respiratory diagnoses. A larger study will be performed to improve risk stratification and enable more selective follow up.